Clinical, MRI, and Genetic Findings in Batten Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The correlation of clinical, MRI and genetic factors in 36 patients with Batten disease (juvenile-onset neuronal ceroid lipofuscinosis) followed up for 25 years is reported from the Department of Paediatric Neurology, University of Helsinki, Finland, and other centers.